Bentuk-Bentuk Etos Kerja dalam Manajemen Pendidikan dan Pendidikan Islam - Ermida, Ermida; Bustaman, Risman (PT PUSTAKA CENDEKIA GROUP, 2023)
The work ethic in Islamic education is very important to understand and apply in your duties as an educator. Work ethic includes ethical behavior in work and management of Islamic education. Work ethic is a guide for decision making in Islamic education management. The work ethic in Islamic education includes moral values and Islamic principles that must be applied in the world of work and management of Islamic education. QS. AlBalad: 4 says